ANALISIS PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT (BPR) DI JAWA TIMUR - Kinar sih; Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2020)
This research aims to analyze the influencing factors lending at the Rural Bank (BPR) in East Java Provience, a total population recorded in desember 2018 of 1583 offices spread in East Java Province. The variable used are Third Party Funds (DPK), BI-Rate, and Non Performing Loan (NPL). The source of this research data comes from the official website of the Central Statistics aviable in the Financial Services Authority (OJK). The period of the research is amounted 14 years, starting from 2005 – 2018. The analysis technique of this research is the Multiple Linear Regression technique. Based on results of this research, it can be stated simultaneously and partyally that the independent variable has a significant effect on lending, when the variable Third Party Funds (DPK) and BI-Rate both have a significant positive effect with probability of 0.0000 and 0.0088. while the Non Performing Loan (NPL) variable has a significant negative effect with a probability of 0.0001